(untitled) (International Journal on Stereo & Immersive Media, 2019)
This paper is intended to give an example of the impact of optical shows in relation to the dissemination of stereoscopy in Spain. Concretely, I will be focusing on a stereoscopic show run by the optician Francisco Dalmau, established in La Rambla in Barcelona, which remained open from 1853 to 1863. Evidence seems to point to the fact that it was the first time that stereo photography was presented as part of an optical show in the city. By analyzing this case, I will attempt to illustrate the visual novelty, the level of acceptance and then great popularity of the stereoscope compared to other entertainment in this period. Finally, I will present new data concerning a stereo photography studio that Dalmau opened in 1854.